Methodological solutions of oral history and their application in research into Czech evangelical communities in Eastern and South-eastern Europe (Theatrum historiae, 2022)
This work deals with the Czech evangelical (reformed religion) communities in Eastern and Southeastern Europe which originated in the 19th century and at the beginning of the 20th for economic and social reasons. The founders of these communities either left the territory of Bohemia and Moravia for the fringes of the Habsburg monarchy (they started to appear abroad only after the creation of Czechoslovakia), or they left the post-White Mountain exiles’ settlements in today’s Poland and set up new villages by the process of what is termed secondary migration. These communities continue to function up to today and the Czech language is still a commonly used form of communication. The aim of this work is to capture the narration of the last members of these communities about the history of particular communities and the common motifs of their narrations across the communities. The factors which help to preserve the identities of these communities are also identified. The method of oral history and the biographical method are the main approaches employed in the research, and the final narrations are analysed and compared. Subsequently, the concepts of the collective memory are taken into consideration.
Keywords: expatriates; oral history; collective memory; ecclesiastical history; Evangelical Church